2006
DOI: 10.1080/00365520500380817
|View full text |Cite
|
Sign up to set email alerts
|

ColoPlus, a new product based on bovine colostrum, alleviates HIV-associated diarrhoea

Abstract: ColoPlus may be an important alternative or additional treatment in HIV-associated diarrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 8 publications
5
67
0
Order By: Relevance
“…Reduction in parasite load was observed in animals given immune colostrum (Fayer et al 1989;Perryman and Bjorneby 1991). In an observational study in Nigeria, HIV-associated diarrhea was alleviated by a 4 week treatment regimen with a commercial bovine colostrum product (Floren et al 2006). Among a 30 patient group with diarrhea, 20 had cryptosporidiosis.…”
Section: Immunotherapeutic Treatment (Colostrum)mentioning
confidence: 99%
“…Reduction in parasite load was observed in animals given immune colostrum (Fayer et al 1989;Perryman and Bjorneby 1991). In an observational study in Nigeria, HIV-associated diarrhea was alleviated by a 4 week treatment regimen with a commercial bovine colostrum product (Floren et al 2006). Among a 30 patient group with diarrhea, 20 had cryptosporidiosis.…”
Section: Immunotherapeutic Treatment (Colostrum)mentioning
confidence: 99%
“…It was further assumed that the proportion of patients with HIV-associated diarrhea whose diarrhea would subside after receiving colostrum-based supplement was 72% [5,9]. Assuming 20% loss to follow up of the calculated sample size (6.4≈7 patients), the minimum sample size for each arm was 39≈40.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…An earlier open-labeled observational study from Nigeria indicated clinical improvement of patients with HIV-associated diarrhea on regular supplementation with ColoPlus® [9].…”
Section: Introductionmentioning
confidence: 97%
“…Some authors have reported lactose intolerance, nausea, flatulence, transient diarrhoea and unspecified abdominal discomfort as possible side effects while other studies specifically reported the absence of side effects (83,128,129,165,137,143,189,190). However, further research is required in order to confirm these data, and, more importantly, to evaluate the effects of colostrum when used for a prolonged periods of time and during pregnancy.…”
Section: Side Effects and Contraindicationsmentioning
confidence: 99%